Investigating how homeopaths and chiropractors navigate patient requests for vaccination information in Ontario, Canada: a qualitative study - Ibukunoluwa Grace Okusanya; Eve Dubé; Eric Filice; Benjamin Malo; Julie Bettinger; Michelle Driedger; Janice Graham; Devon Greyson; Greg Kawchuk; Noni MacDonald; Shannon MacDonald; Samantha B. Meyer (Archives of Public Health)
Abstract Background. Chiropractors and homeopaths are trusted sources of health information for many Canadians, including around vaccination. However, within Ontario, Canada, the College of Chiropractors of Ontario and the College of Homeopaths of Ontario regulations state that vaccines are not within their scope of practice and providers should not express views, treat, or advise patients with respect to vaccination. The aims of the present study were to: (1) describe the attitudes and beliefs regarding vaccination held among participating chiropractors and homeopaths; (2) identify the sources of information about vaccination they trust and use to guide their personal vaccination decisions; and (3) describe how they navigate patient requests for guidance on vaccine decision-making within the current regulatory landscape. Methods. Semi-structured interviews (N = 16) were conducted between February 2020-March 2021 and explored participants’ opinions on vaccination, sources of information they trust and recommend to their patients, and how they navigate vaccine conversations with patients. Results. Providers’ personal beliefs regarding vaccination were described as reinforced by social and professional networks, through their personal experiences, and in consultation with clients. Various strategies were used to support patients while abiding by regulations (e.g. referring patients to providers for whom vaccination is within their scope of practice); however, other strategies described (e.g., stating personal beliefs) could be interpreted as a breach of regulation. Conclusions. This research reinforces existing literature suggesting that patients using chiropractors and homeopaths have questions about vaccination and are looking for trusted information. Public health services should consider engaging with chiropractors and homeopaths to facilitate communication between patients and immunization providers.